OPTIMIZATION OF MEDIATION IN CHILD CUSTODY DISPUTES: EFFORTS TO REALIZE THE PROTECTION AND BEST INTERESTS OF THE CHILD - Hikmatiar Harahap; Bagus Ramadi (Journal of Gender and Social Inclusion in Muslim Societies, 2026)
Child custody disputes following divorce frequently neglect the fundamental rights and psychological well being of the child, resulting in prolonged legal battles that prioritize parental ego over child welfare. This study aims to extensively analyze the optimization of the mediation process in child custody disputes as a primary and indispensable instrument to realize the legal protection and the best interests of the child. Employing a normative legal research method with statutory, conceptual, and case-based approaches, this study reviews relevant literature, Supreme Court regulations (PERMA No. 1 of 2016), and recent jurisprudential developments. The results indicate that while litigation ends in adversarial win-lose outcomes, mediation provides a collaborative, non-litigation alternative that fosters rational decision-making and sustainable parenting arrangements. Statistical and jurisprudential analysis reveals that successful mediation significantly reduces post-divorce conflict and ensures continuity in child development. This research introduces a novel framework by integrating therapeutic and facilitative mediation models specifically tailored for Indonesian courts, addressing the current gap in mediator competence and psychological intervention. In conclusion, optimizing mediation requires specialized training for mediators in child psychology and a mandatory, structured pre-mediation phase. It is highly recommended that future policies mandate psychological assessment as an integral part of the mediation process to strictly uphold the child's best interests